The change in the frequency of community acquired acute respiratory tract infections in weight loss period after bariatric surgery: An observational casecrossover study. Are those who have had bariatric surgery at risk? - Coşkun, Serdar; Kırkıl, Cüneyt; Kirkil, Gamze (My University, 2021)
Aim: It is unknown whether there is an increase in the frequency of acquired respiratory tract infections (ARTIs) \rwhile the weight loss process continues after bariatric surgery (BS). \rMethods: An observational case-crossover study of 366 patients underwent BS between September 2018 and \rSeptember 2019 was performed. Prospectively recorded data of ARTI events in the first pre- and post-operative \rARTI seasons were compared.\rResults: Mean age was 36.4 ± 10.9 years and mean body mass index (BMI) was 44.1 ± 6.2 kg/m2. Mean change \rin BMI in an ARTI season was 13.2 ± 6.1 kg/m2. Among 366 patients, 180 (49.2%) were diagnosed with ARTI \rand the average numbers of ARTIs was 0.69 ± 0.85 in preoperative season. During the postoperative season, 134 \r(36.6%) patients were diagnosed with ARTI and the average numbers of ARTIs was 0.49 ± 0.76. Both period \rprevalence and average number of ARTIs in preoperative ARTI season was significantly higher than \rpostoperative season (P = 0.001 for both). The change in BMI in an ARTI season was correlated with the \rpostoperative period prevalence of ARTIs (r = 0.119, p = 0.022).\rConclusion: These findings showed that the period prevalence and incidence of ARTIs reduced after BS. \rHowever, the frequency of ARTIs was higher in patients with greater weight loss.
Keywords: Solunum Sistemi; Genel ve Dahili Tıp